2023
DOI: 10.1142/s1752890922420107
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Quantification to Improve the Classification of Melanoma and Basal Skin Cancer Using ResNet Model

Abstract: Traditional skin cancer screening necessitates a time-consuming physical examination by a dermatologist. One of the most difficult tasks in image analysis is automated medical picture recognition and categorization. Making a skin-based analysis to predict the abnormalities present in a particular area is always a competitive issue. In the case of automatic region identification, deep learning (DL) methodologies play a major role. Most DL approaches are unable to offer uncertainty quantification (UQ) for the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The MC dropout technique adeptly identified out-of-domain data, reducing training time. Consequently, the ResNet50 model achieved an impressive 89% accuracy in skin cancer classification [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The MC dropout technique adeptly identified out-of-domain data, reducing training time. Consequently, the ResNet50 model achieved an impressive 89% accuracy in skin cancer classification [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also incorporated transfer learning, and their results showed that the proposed model achieved an accuracy of 96.5%, 98%, and 89% for the HAM10000, ISBI2018, and ISIC2019 datasets, respectively. In another study, Deepa et al [36] trained the ResNet50 model on the International Skin Image Collaboration (ISIC) dataset and achieved 89% accuracy. Tahir et al [37] proposed a deep learning model called DSCC_Net, trained that on three datasets, ISIC 2020, HAM10000, and DermIS, and achieved an accuracy of 99%.…”
Section: Introductionmentioning
confidence: 99%